Production of coated salted dry roasted peanuts - Ang, Agnes Marie Naval (1998)
Gluten-dextrin, sorbitol-mannitol, and gum arabic solutions were used for coating dry roasted peanuts with 1%, 2%, and 3% salt. Hygroscopicity of the coated peanut samples was determined by exposing samples to the atmosphere for a period of 24 hours. Sensory evaluation was conducted on the coated samples everyday for 10 days using 24 consumer panelists. Appearance, saltiness, crunchiness, rancidity, and overall acceptability were evaluated. Results indicated that salt concentration has no significant effect on the sensory attributes of the coated salted dry roasted peanuts. However, the coating agent used significantly affected the sensory characteristics of the coated peanuts. Dry roasted peanuts coated with salt using gluten-dextrin solution as coating agent obtained the most favorable sensory quality compared with the other coated nutmeats.